2019
DOI: 10.1007/s12039-019-1604-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel enzymatic biosensor for detection of intracellular hydrogen peroxide based on 1-aminopyrene and reduced graphene oxides

Abstract: An electrochemical sensor for hydrogen peroxide (H 2 O 2) detection was established using 1aminopyrene (AP) as a linker between horseradish peroxidase (HRP) and reduced graphene oxides (rGO) modified glassy carbon electrode. The AP can combine with HRP via a covalent bond and combine with rGO via π-π conjugation. The covalent bond linkages can prevent the enzymes leaching of the enzymes and the π-π conjugate combination can facilitate electrons transfer, which plays synergistic effects to improve the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The immobilised biomolecules at the electrode surfaces could be achieved either using physical adsorption, self-assembly monolayer, polymer coating or covalent immobilisation methods. 41 The targeted analytes could be cancer biomarkers, 41 viruses, 42 cardiac biomarkers, 43,44 glucose, 45 hydrogen peroxide (H 2 O 2 ), 46 foodborne pathogens 47 and heavy metal ions. 48 The common electrode substrates used to construct the immobilised biomolecule probes are GC electrode, 49 gold electrode, 50,51 screen-printed carbon electrode (SPCE) 52,53 and indium tin oxide (ITO) electrode.…”
Section: Polymer/carbon Nanomaterials 3d-printed Electrodes For Elect...mentioning
confidence: 99%
“…The immobilised biomolecules at the electrode surfaces could be achieved either using physical adsorption, self-assembly monolayer, polymer coating or covalent immobilisation methods. 41 The targeted analytes could be cancer biomarkers, 41 viruses, 42 cardiac biomarkers, 43,44 glucose, 45 hydrogen peroxide (H 2 O 2 ), 46 foodborne pathogens 47 and heavy metal ions. 48 The common electrode substrates used to construct the immobilised biomolecule probes are GC electrode, 49 gold electrode, 50,51 screen-printed carbon electrode (SPCE) 52,53 and indium tin oxide (ITO) electrode.…”
Section: Polymer/carbon Nanomaterials 3d-printed Electrodes For Elect...mentioning
confidence: 99%
“…136 In yet another study, HRP-AP/ rGO (AP: 1-aminopyrene as a linker between HRP and rGO) modified glassy carbon electrode was used for intracellular hydrogen peroxide detection. 137 Though bioreceptor based (bio)sensors are famous for their inherent specific activity, they suffer from disadvantages like high cost of bioreceptors, loss in their activity with time, and other physiological parameters. Consequently, these are not quite successful for field applications, which limits their usage.…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
“…Magyar et al used indium tin oxide (ITO) functionalized with multiwalled carbon nanotubes (MWCNTs) and horseradish peroxidase (HRP) for the real time measurements of hydrogen peroxide . In yet another study, HRP-AP/rGO (AP: 1-aminopyrene as a linker between HRP and rGO) modified glassy carbon electrode was used for intracellular hydrogen peroxide detection . Though bioreceptor based (bio)­sensors are famous for their inherent specific activity, they suffer from disadvantages like high cost of bioreceptors, loss in their activity with time, and other physiological parameters.…”
Section: D Layered Materials Based (Bio)sensors For Oxidative Stress ...mentioning
confidence: 99%
“…Recently, Zou et al showed the detection of H2O2 by immobilizing horseradish peroxidase (HRP) on rGO using aminopyrene (AP) as a linker. The covalent bond between AP and HRP, and the π – π interactions between AP and rGO sheets resulted in improved electron transfer across the nanocomposite, enabling suitable detection of H2O2 [58]. Other nanocomposites involving rGO nanosheets have been reported in Refs.…”
Section: Graphene/graphene Oxide Nanomaterials Based Electrochemicmentioning
confidence: 99%